PoSW:novel secure deduplication scheme for collaborative cloud applications - Jin-bo XIONG; Su-ping LI; Yuan-yuan ZHANG; Xuan LI; EA-yong Y; Zhi-qiang YAO (Tongxin xuebao)
In order to solve the problems of secure access and deduplication to the shared file in the cloud environment,a novel notion called proof of shared ownership (PoSW) was formalized,and a formal definition of the PoSW was given.Furthermore,a PoSW scheme and an enhanced version of that were proposed.In the PoSW scheme,secure shared file dispersal,convergent encryption and secret sharing algorithm were employed to transform the shared file realize the sharing and authorization for the shared file,and then a novel challenge-response protocol was proposed to achieve the proof of shared ownership and the foundation for the secure deduplication of the shared file was provided.An enhanced PoSW scheme was designed to improve the availability and reliability for different kinds of the shared files by introducing the multi-cloud server providers and using the strategies of both data duplication and secret file dispersal.Security analysis and performance evaluation show the security and efficiency of the proposed scheme.